Immunotoxicity of Pembrolizumab in patients with metastatic non-small cell lung cancer: A single-centre study - Stojanović, Miloš; Bursać, Daliborka (Archive of Oncology, 2024)
Background: Immunotherapy represents a new form of treatment, that stimulates immune system to destroy cancer cells. Pembrolizumab is a humanized monoclonal antibody that binds to the PD-1 programmed cell death receptor and blocks its interaction with the PD-L1 and PD-L2 ligands. The aim of this study was to determine the efficacy and safety of the drug pembrolizumab, in the first line of treatment in patients with metastatic NSCLC. Methods: The research was retrospective and was conducted at the Institute for Pulmonary Diseases of Vojvodina, it included patients treated in the period from January 2018 to December 2019, in whom metastatic NSCLC was verified. Results: The study included a total of 20 patients, 10 men and 10 women. The average age was 61.75 years. The average length of therapy was 15 cycles (45 weeks), the minimum was 1, and the maximum was 33. 12 patients (60%) had a lethal outcome. The median time to disease progression was 8.1 months and overall survival was 14.6 months. Of the total number of patients, 13 (65%) had side effects to pembrolizumab therapy, and 7 (35%) did not experience any. Out of a total of 13 patients who had side effects, 9 had only one isolated, 4 had more associated side effects, of which 3 patients had 2 associated, and 1 patient had 3 associated side effects. Conclusion: Based on the results, immunotherapy certainly occupies an important place in the treatment of metastatic NSCLC. Namely, the lack of severe side effects linked to cytotoxic chemotherapy and the relative ease of treating immune related adverse effects (irAEs) that occur with immunotherapy, good overall survival and later onset of disease progression opens the door to the possibility of a better quality of life for these patients and the prolongation of their lifespan.